An Analysis of Cost Efficiency and Determinants of Profitability in Hong Kong Commercial Banks - Chen, Zhuo (2016)
This paper examines the cost efficiency and determinants of profitability of 19 commercial banks in Hong Kong for the period 2008 to 2015. The normalised translog models of COLS and MOLS are used to estimate cost efficiency. Two-step GMM is used to examine the factors that have an impact on the profitability of the Hong Kong banking sector. It is found that the overall cost efficiency score is high and small banks are more efficient than large ones. However, cost efficiency does not affect profitability of banks. Bank size and concentration have significant impacts on profitability, which indicates that although large banks would spend more on agency costs and information costs, they could still gain profits because large banks have market power and monopoly power. The paper also discovers that Hong Kong banks’ credit quality and capital adequacy and inflation of the Hong Kong financial market are related to banks’ profits. In addition, this paper also combined some regulations, for example Basel III to analysis the variables which have effect on banks profitability.